Designing and engineering through collaboration and negotiation. (24th July 2009) - Suh, N.P.
The development of complex engineering systems requires collaboration and negotiation. It is to make correct decisions based on customer needs, Functional Requirements, Design Parameters, and Process Variables. There are two basic elements: the system and the process used for collaboration and negotiation. The system is to assure that the project has the best information and knowledge. Systems and processes are needed to minimise the cost of development, to execute the project on schedule, and to deliver a highly robust, efficient and reliable product. This paper proposes heuristic rules for collaboration and negotiation based on axiomatic design theory and complexity theory.